2018
DOI: 10.1111/jcpe.13024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms and fragments of salivary MMP‐8 in relation to periodontitis

Abstract: Aim To investigate the molecular forms of salivary matrix metalloproteinase (MMP)‐8 in relation to periodontitis. Materials and Methods Molecular forms, degree of activation and fragmentation of neutrophilic and mesenchymal‐type MMP‐8 isoforms were analysed from salivary samples of 81 subjects with generalized periodontitis, 63 subjects with localized periodontitis and 79 subjects without pocket teeth, by using western‐immunoblots with computer quantitation. In addition, human recombinant proMMP‐8 was in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 35 publications
(57 reference statements)
6
43
1
1
Order By: Relevance
“…Studies have detected MMP‐8 in saliva and GCF of periodontitis patients and in PICF of PIP patients suggestive that MMP‐8 levels may be useful for diagnostic monitoring of the connective tissue destruction phase of peri‐implant disease. MMP‐8, including targeting its active form, has been reported to represent a valuable target for chairside point‐of‐care testing of oral fluids related to detection of periodontitis, and more recently in PIP; albeit active MMP‐8’s ability to affect treatment decision‐making remains to be fully elucidated and implemented within the global dental profession. Similar to our findings, Wang et al did not observe significant differences in the concentration of MMP‐8 between healthy and PIP individuals, although the literature would support that differences in selection of antibody systems to detect these types of biomolecules can create variation in the levels and outcome measures between health and disease .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have detected MMP‐8 in saliva and GCF of periodontitis patients and in PICF of PIP patients suggestive that MMP‐8 levels may be useful for diagnostic monitoring of the connective tissue destruction phase of peri‐implant disease. MMP‐8, including targeting its active form, has been reported to represent a valuable target for chairside point‐of‐care testing of oral fluids related to detection of periodontitis, and more recently in PIP; albeit active MMP‐8’s ability to affect treatment decision‐making remains to be fully elucidated and implemented within the global dental profession. Similar to our findings, Wang et al did not observe significant differences in the concentration of MMP‐8 between healthy and PIP individuals, although the literature would support that differences in selection of antibody systems to detect these types of biomolecules can create variation in the levels and outcome measures between health and disease .…”
Section: Discussionmentioning
confidence: 99%
“…While various studies already demonstrated the presence of aMMP‐8 in periodontitis, the current study demonstrated for the first time that MMP‐8 is not activated during the induction and resolution of experimentally‐induced gingival inflammation, but rather exists in its latent proMMP‐8 form. We have used WB analysis to assess the molecular forms of MMP‐8 utilizing a polyclonal anti‐MMP‐8 antibody to specifically detect different MMP‐8 (complexes, pro and active forms, and smaller fragments) molecules by their molecular sizes and forms. For all saliva samples, the predominant molecular form identified by WB analysis was the full‐size pro‐form of MMP‐8, while no lower molecular size (20–55 kDa) MMP‐8 forms were detected throughout the study.…”
Section: Discussionmentioning
confidence: 44%
“…Since aMMP‐8, rather than the overall amount of MMP‐8, is strongly associated with the pathological destruction of connective tissue in periodontitis, the investigation of the degree of MMP‐8 activation, that is, conversion and fragmentation of latent 70–75 kDa proMMP‐8 to lower molecular size active and fragmented MMP‐8 20–55 kDa forms, is a very important and key issue . While various studies already demonstrated the presence of aMMP‐8 in periodontitis, the current study demonstrated for the first time that MMP‐8 is not activated during the induction and resolution of experimentally‐induced gingival inflammation, but rather exists in its latent proMMP‐8 form. We have used WB analysis to assess the molecular forms of MMP‐8 utilizing a polyclonal anti‐MMP‐8 antibody to specifically detect different MMP‐8 (complexes, pro and active forms, and smaller fragments) molecules by their molecular sizes and forms.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations